A Bioorthogonal Reaction of N‐Oxide and Boron Reagents. (16th November 2015) - Kim, Justin; Bertozzi, Carolyn R.
Abstract: The development of bioorthogonal reactions has classically focused on bond‐forming ligation reactions. In this report, we seek to expand the functional repertoire of such transformations by introducing a new bond‐cleaving reaction between N ‐oxide and boron reagents. The reaction features a large dynamic range of reactivity, showcasing second‐order rate constants as high as 2.3×10 3  M −1  s −1 using diboron reaction partners. Diboron reagents display minimal cell toxicity at millimolar concentrations, penetrate cell membranes, and effectively reduce N ‐oxides inside mammalian cells. This new bioorthogonal process based on miniscule components is thus well‐suited for activating molecules within cells under chemical control. Furthermore, we demonstrate that the metabolic diversity of nature enables the use of naturally occurring functional groups that display inherent biocompatibility alongside abiotic components for organism‐specific applications. Abstract : Die bindungsspaltende Reaktion zwischen N ‐Oxid‐ und Dibor‐Reagentien verläuft mit Geschwindigkeitskonstanten zweiter Ordnung bis zu 2.3×10 3  M −1  s −1 . Dibor‐Reagentien sind bei millimolaren Konzentrationen kaum zytotoxisch, durchdringen Zellmembranen, und reduzieren N ‐Oxide in Säugetierzellen. Diese neue bioorthogonale Reaktion ist daher für die chemische Aktivierung von Molekülen in Zellen gut geeignet.